QUIET QUITTING IN THE NIGERIAN HEALTHCARE SECTOR: INVESTIGATING UNDERLYING MOTIVES AND CONSEQUENCES ON CORPORATE PRODUCTIVITY - YISA, Yusuf Olamitunji; AREMU, Nuha Salihu; ABOGUNRIN, Peter Abiodun (Journal of process management and new technologies, 2024)
Quiet quitting has become one of the prevailing workers attitudes affecting the productivity in many business organizations. Considering its prevalence in the healthcare sector, the present research seeks to investigate the underlying motives for quiet quitting among health workers and its consequences on corporate productivity in the Nigerian health sector. Adopting a quantitative methodology, the research utilized a well-structured questionnaire, and data was collected from the seventy-four staff of Lagos State University Teaching Hospital in Nigeria. In analyzing the research data, descriptive and inferential statistics was used to evaluate and predict the causes and consequences of quiet quitting among healthcare workers the Nigerian business industry. The findings of the study revealed that excessive workload emerged as a primal significant factor influencing quiet quitting behaviors, impacting job satisfaction and retention. Notably, the result highlights the long-term implications of silent disengagement, accentuating its enduring consequences. Although, the correlation between compensation and quiet quitting underscored the pivotal role of fair remuneration in addressing employee disengagement. Meanwhile, the emphasis on pays and rewards underscores the critical relevance of equitable compensation structures in improving staff engagement and retention in the Nigerian healthcare sector. Recognizing the impact of compensation on silent quitting habits, Nigeria government and public administrators are advised to plan and implement initiatives to ensure fair remuneration, potentially reducing disengagement and enhancing commitment among healthcare workers.